Low-intensity physical activity may protect pregnant women against spontaneous preterm labour: a prospective case-control study - Steckle, Valerie; Shynlova, Oksana; Lye, Stephen; Bocking, Alan (Applied physiology, nutrition, and metabolism, 2021)
The innate immune system plays a significant role in onset of parturition. Maternal antenatal physical activity can influence immune function and timing of labour. We examined physical activity patterns and concentration of 19 cytokines at 16 and 27 weeks gestational age (GA), in peripheral plasma of 28 asymptomatic women who later had spontaneous preterm labour (SPTL, <37 weeks GA) and 52 women who later delivered at term (TL; ≥37 weeks GA). This nested case-control study used data from the Ontario Birth Study cohort. Exercise was assessed using the International Physical Activity Questionnaire, and cytokines were analyzed using Luminex assays. There was no significant difference in exercise patterns between SPTL and TL subjects. Plasma concentration of interleukin (IL)-10 was significantly higher in SPTL women at 16 and 27 weeks, while tumour necrosis factor alpha (TNF-α), IL-8, and monocyte chemoattractant protein (MCP)-1 concentrations were increased at 27 weeks GA (p < 0.05). Concentration of IL-10 was negatively correlated with the amount of reported walking (ρ = −0.264, p = 0.03). Women should be encouraged to partake in low-intensity exercise throughout pregnancy, as it may confer a protective effect against SPTL through IL-10–mediated pathways. Additionally, plasma cytokine analysis at 27 weeks GA may be useful for predicting SPTL in asymptomatic women. Novelty: In women that delivered preterm, plasma levels of anti-inflammatory cytokine IL-10 were significantly elevated at 16 and 27 weeks of gestation. Plasma levels of IL-10 were negatively correlated with the amount of reported walking. Concentration of IL-8, MCP-1 and TNF-α were increased in plasma of asymptomatic women that subsequently deliver preterm.